Predictive Testing for Tumor Predisposition Syndromes in Pediatric Relatives: An Asian Experience - Chiang, Jianbang; Yuen, Jeanette; Shaw, Tarryn; Goh, Hui Xuan; Li, Shao-Tzu; Courtney, Eliza; Ngeow, Joanne (Frontiers in Pediatrics, 2020)
Approximately 10% of pediatric cancer patients possess germline pathogenic/likely pathogenic variants (PV/LPV) in known tumor predisposition genes. Predictive testing is the optimal approach to identify asymptomatic at-risk relatives to guide gene-directed surveillance for early cancer detection and/or risk-reducing strategies. However, the uptake rate for predictive testing remains low in Asian countries. We aim to evaluate the uptake rate of predictive testing in a pediatric population (aged under 21-years-old) in a multi-ethnic Asian cancer centre. Our retrospective analysis included families with PV/LPVs identified in genes associated with pediatric tumour predisposition. Of the 83 pediatric first-degree relatives (FDRs) from 49 unrelated families, 20 FDRs (24.1%) originating from 13 families (26.6%) underwent predictive testing. Genes tested in pediatric FDRs were APC, RB1, SBDS, SDHA, SDHB, SDHD, and TP53. All pediatric FDRs of probands with PV/LPVs in RB1 and biallelic PVs in SBDS underwent predictive testing, while less than 45% of pediatric FDRs had predictive testing for familial PV/LPVs identified in the APC, SDHA, SDHB, SDHD, and TP53 genes. Amongst the 13 families who underwent pre-test counseling, 80% of pediatric FDRs in these families proceeded with predictive testing. Malay pediatric FDRs and siblings of probands were more likely to undergo predictive testing. We conclude that the predictive testing rate in pediatric FDRs is higher than that of adult FDRs in Asia, but still below the global average. We postulate factors that may influence predictive testing uptake in pediatric FDRs includes a lack of genetics awareness, concerns regarding insurance, and genetic discrimination.